PLAC8 Overexpression Promotes Lung Cancer Cell Growth via Wnt/β-Catenin Signaling. (22nd April 2022) - Chen, Wei; Wu, Junlu; Wang, Weiwei; Yu, Li; Xu, Xianghuai
Abstract : The PLAC8 expression in lung cancer tissues and in vitro grown lung cancer cells, as well as the involvement of the Wnt/ β -Catenin signaling pathway, was investigated in this process. PLAC8 protein expression in human lung cancer tissues and lung tumor cells of different strains was discovered using immunohistochemistry staining and Western blot, respectively. Animal models of PLAC8 overexpression and knockdown were created using lentivirus. The development in tumor tissue was seen both in vitro and vivo. The Wnt/ β -Catenin signaling pathway played an important part in this process, as shown by the dual luciferase reporter gene system. PLAC8 expression was elevated in lung cancer tissues and plasma and decreased in plasma after lung tumor resection. PLAC8 upregulation promotes cell proliferation in vivo and in vitro, while PLAC8 downregulation inhibits cell viability and proliferation. The results of the dual luciferase reporter gene system suggest that PLAC8 can significantly activate the Wnt/ β -Catenin signaling pathway in cells and can conduct signaling through it. A potential treatment targeting the prognosis of lung cancer patients may be PLAC8 overexpression, which promotes the lung cancer cell proliferation through controlling the Wnt/ β -Catenin signaling pathway.